1969
DOI: 10.1080/00268976900101301
|View full text |Cite
|
Sign up to set email alerts
|

ENDOR of biradicals

Abstract: The ENDOR spectra of Tschitschibabin's hydrocarbon and certain of its specifically deuterated derivatives have been measured. To interpret these spectra the factors determining the ENDOR spectrum of a biradical are discussed in detail. The analysis reveals that the paramagnetic species present in solutions of Tschitschibabin's hydrocarbon and responsible for the solution electron resonance spectrum is a substituted p-biphenyldiphenylmethyl radical, thus resolving the biradical paradox. The substituent is thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…According to X-ray analysis, 18 adapted a nearly planar form with a large bond length alternation in the quinoid framework, and showed no detectable ESR signal in the solution and solid state. 39 In contrast, the presence of ESR signals in the solution and solid states for quaterphenoquinone (19) 40 and quinquephenoquinone (20) 41 implies that these compounds have appreciable biradical character. Because 19 and 20 appear to adapt predominantly a diamagnetic quinoid form in the solid state by SQUID measurements, thermally excited triplet species may be responsible for the solid-state ESR signals.…”
Section: ¹1mentioning
confidence: 88%
See 1 more Smart Citation
“…According to X-ray analysis, 18 adapted a nearly planar form with a large bond length alternation in the quinoid framework, and showed no detectable ESR signal in the solution and solid state. 39 In contrast, the presence of ESR signals in the solution and solid states for quaterphenoquinone (19) 40 and quinquephenoquinone (20) 41 implies that these compounds have appreciable biradical character. Because 19 and 20 appear to adapt predominantly a diamagnetic quinoid form in the solid state by SQUID measurements, thermally excited triplet species may be responsible for the solid-state ESR signals.…”
Section: ¹1mentioning
confidence: 88%
“…4%) of triplet species, evoking the issue "The Biradical Paradox." 17 In 1964, this controversial issue was partially resolved by further ESR studies, from which it was concluded that the paramagnetic species are derived from a dimer or higher polymer of 2, 18 and in 1969 a hydrogen abstracted molecule was proposed as another candidate for the paramagnetic species on the basis of ENDOR studies by Brauer et al 19 The conclusive remark was finally given by Montgomery et al in 1986, 20 who demonstrated that 2 adapts a singlet quinoidal structure with an apparent manifestation of biradical character in the ground state, by X-ray singlecrystal analysis. An ESR measurement of the pure 2 gave no signal at 77 K.…”
Section: ¹1mentioning
confidence: 99%
“…Brauer et al did extensive ENDOR studies and suggested that the spectrum originated from a monoradical impurity with structural formula shown in Figure 2a. 23,25 Along with this van der Hart and Oosterhoff suggested dimers of the biradicals (Figure 2b), responsible for the observed EPR spectrum. 26 Thus the reported EPR spectrum with vanishing exchange interactions (J < 10 8 Hz) could be imputed to impurities thereby solving the biradical paradox of Tschitschibabin's HC.…”
Section: Introductionmentioning
confidence: 87%
“…The point is that theory predicts J = 15 x 10 6 MHz for electron -electron interaction in biradicals of the type of Chichibabin's hydrocarbon, while the experimental value is only 70 MHz. The problem was solved by analysing the ENDOR spectra 140 .…”
Section: Biradicalsmentioning
confidence: 99%